Exploring Character Education Values in the Ziarah Kubro Tradition as a Local Wisdom Heritage in Palembang - Batrisyia Afrina; Cecep Darmawan; Rika Sartika; Junaidi Junaidi (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Globalization and digitalization have significantly impacted youth, influencing their moral, social, and cultural behaviors. Local traditions, however, remain a vital medium for transmitting values that foster character development. This study explores the character education values embedded in the Ziarah Kubro tradition, a cultural and religious practice in Palembang, Indonesia, and examines its relevance for contemporary youth. Using a qualitative descriptive design, five youth participants aged 18–25 were selected through purposive sampling. Data were collected via semi-structured interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña, incorporating triangulation to ensure validity. Findings indicate that the tradition fosters religiosity, empathy, social respect, solidarity, cooperative behavior, and cultural identity among youth. Moreover, despite the prevalence of digital media, Ziarah Kubro remains relevant, bridging historical knowledge, spiritual growth, and social engagement. The study demonstrates that local cultural practices can effectively serve as a foundation for character education while adapting to contemporary digital contexts. These insights provide both theoretical contributions to the understanding of culturally grounded character education and practical guidance for educators and community leaders in preserving local heritage.